2010
DOI: 10.1177/082585971002600208
|View full text |Cite
|
Sign up to set email alerts
|

Care Provider Perspectives on End-Of-Life Care in Long-Term-Care Homes: Implications for Whole-Person and Palliative Care

Abstract: This study holistically explores the experience of dying and end-of-life care for older persons with dementia in long-term care (LTC) from the perspective of care providers. Using a focused ethnography methodology, seven researchers interviewed LTC staff, residents’ families, volunteers, management staff, and spiritual advisers/clergy over a five-day period. Research was guided by two key questions: What is the dying experience of people living in LTC from the perspective of different care providers? and, What… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 11 publications
0
39
0
2
Order By: Relevance
“…This indicates the need for quality improvement because early discussion of goals of care is a best practice in providing EOLC to elderly people with serious illness [91, 92]. The overall QPC-LTC research identified that most LTC staff were not comfortable having advance care planning and EOL conversations with residents and families [27, 28, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates the need for quality improvement because early discussion of goals of care is a best practice in providing EOLC to elderly people with serious illness [91, 92]. The overall QPC-LTC research identified that most LTC staff were not comfortable having advance care planning and EOL conversations with residents and families [27, 28, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Data were mostly derived from care homes, hospitals, hospice care facilities, Specialists PC service, general practices and residential care homes (See supplementary file online). Out of all the studies, 29 derived data from healthcare professionals/providers [30-38, 40-53, 55-57, 59, 60, 62], 11 from managers/directors of care facilities [34-36, 43, 44, 46, 47, 52, 57, 60, 61], nine studies from carers/caregivers [29,38,42,45,54,[56][57][58][59], one study from the patient's perspective [54] and seven focused on the commissioner's and policy expert's perspectives [35,36,39,43,44,46,56]. See also barriers to provision of PC from different stakeholders' perspectives in the online supplementary file for further details.…”
Section: Country Setting and Participantsmentioning
confidence: 99%
“…Constraints. (4) [32,35,41,57] Dementia is not considered worthy of PC [55]. Lack of consistency at workplace [43].…”
Section: Timementioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews have shown a considerable need for palliative care in these settings, including the need for improved symptom management[2-4] and addressing psychosocial and spiritual needs [3,5]. There are, however, barriers to providing palliative care in care homes, for example: staff shortages and turnover; lack of time and knowledge of palliative care among staff; shortage of equipment; lack of support from primary care; and poor communication among staff, and between staff and residents and their families [6-8]. Some of these are likely to be encountered across different countries, however, since the systems of care and support for residents are different (e.g.…”
Section: Introductionmentioning
confidence: 99%